2009
DOI: 10.1002/jcp.21918
|View full text |Cite
|
Sign up to set email alerts
|

Heterogeneity of non‐cycling and cycling synchronized murine hematopoietic stem/progenitor cells

Abstract: Purified long-term multilineage repopulating marrow stem cells have been considered to be homogenous, but functionally these cells are heterogeneous. Many investigators urge clonal studies to define stem cells but, if stem cells are truly heterogeneous, clonal studies can only define heterogeneity. We have determined the colony growth and differentiation of individual lineage negative, rhodamine low, Hoechst low (LRH) stem cells at various times in cytokine culture, corresponding to specific cell cycle stages.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 28 publications
0
10
0
Order By: Relevance
“…Lineage choice in precursor cells may require cells to go through a replicative cycle ( 94 98 ). Recent studies have suggested that the lineage biases in differentiation of hematopoietic ( 99 ) or embryonic stem cells ( 100 , 101 ) may vary with progression of the cell cycle. In particular, studies of colony formation from HSC expanded in a cytokine mixture in vitro indicated that megakaryocytes may preferentially be produced from cells early in the S phase at about the same time as proliferative granulocytes, while non-proliferative granulocytes are produced by cells in mid-S phase ( 102 ).…”
Section: Discussionmentioning
confidence: 99%
“…Lineage choice in precursor cells may require cells to go through a replicative cycle ( 94 98 ). Recent studies have suggested that the lineage biases in differentiation of hematopoietic ( 99 ) or embryonic stem cells ( 100 , 101 ) may vary with progression of the cell cycle. In particular, studies of colony formation from HSC expanded in a cytokine mixture in vitro indicated that megakaryocytes may preferentially be produced from cells early in the S phase at about the same time as proliferative granulocytes, while non-proliferative granulocytes are produced by cells in mid-S phase ( 102 ).…”
Section: Discussionmentioning
confidence: 99%
“…The influence of microvesicles on cytokine-stimulated cells at different points in cell cycle represents another example of cycle-related phenotype alteration of marrow-derived stem/progenitor cells. We have shown that global gene expression, the expression profile of adhesion proteins and cytokine receptors, homing to marrow after transplantation and short-and long-term multi-lineage engraftment are all linked to changes in cell cycle [1][2][3][4][5][6][7][8][9][10][11][12][13][14]. Differentiation potential of marrow-derived stem-progenitor cells are also linked to cell cycle as evidenced by their ability to preferentially form megakaryocytes and granulocytes in vitro and convert into pulmonary epithelial cells after transplantation into irradiated mice [15][16][17][18][19][20][21][22][23].…”
Section: Discussionmentioning
confidence: 99%
“…With subsequent divisions, daughter cells obtain more differentiated characteristics and lose self-renewal potential. Contrary to this model, our group has shown that HSC are capable of reversibly changing their functional phenotype as they progress though cell cycle [1][2][3][4][5][6][7][8][9][10][11][12][13]. We have used cocktails of cytokines including interleukins (ILs)-3, 6, and 11 and stem cell factor (SCF) or SCF, thrombopoietin, and FLK-2, to induce HSC to progress though cell cycle in a synchronous fashion.…”
mentioning
confidence: 99%
“…For example, mouse adult HSCs are able to reversibly switch between states of dormancy (where they retain the potential for selfrenewal) to a state of active self-renewal during homeostasis or in response to stress (39 -41) . Defi ning SCs and their heterogeneity can also be problematic as even within a defi ned population of SCs they may display heterogeneity at different points in their cell cycle (as seen in mouse marrow SCs) (42) . Current evidence for intestinal SCs, which serves as one of the most actively cycling and regenerating tissues of the body, indicates the existence of two populations of SCs, one of which is a long-term quiescent population (and may be activated in response to injury) and the other is actively cycling and may be involved in regeneration of the tissue (43 -45) .…”
Section: Why Have Advances In Addressing Ish Been So Slow ? Lrc Assaymentioning
confidence: 99%